PENGARUH PUNISHMENT DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BPR ARTHA SINAR RAHARJA INDONESIA KABUPATEN BADUNG - Ni Luh Gede Putu Purnawati; Putu Pande Yudiastra (Universitas Mahendradatta, 2025)
In managing a business, it is hoped that you will be able to use human resourcesproperly and correctly. Human resources are quite an important part in achieving companygoals and are also the main driver of all activities in achieving company goals.This research aims to determine the effect of punishment and workload on employeeperformance at PT BPR Artha Sinar Raharja Indonesia, Badung Regency. The population inthis study was 35 employees at PT. BPR Artha Sinar Raharja. Sample selection using saturatedsampling. The analysis technique used in this research is multiple regression analysis.The results of the research are that Punishment has a positive and significant effect onEmployee Performance at PT. BPR Artha Sinar Raharja, Workload has a positive andsignificant effect on Employee Performance at PT. BPR Artha Sinar Raharja.